La dénomination des mers du postglaciaire au Québec - Dionne, Jean-Claude (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1972)
The denomination of Postglacial seas in Québec is discussed. Champlain and Laflamme seas correspond to relatively short periods of marine invasions of inland areas, while Goldthwait, Iberville and Tyrrell seas correspond to longer marine invasion of coastal areas probably still affected by submergence. For more clarity in the stratigraphical nomenclature, it is appropriate to subdivide these events into two or three distinct periods.